A rapid review of measures to support people in isolation or quarantine during the Covid‐19 pandemic and the effectiveness of such measures. (14th May 2021) - Cardwell, Karen; O'Neill, Sinéad M.; Tyner, Barrie; Broderick, Natasha; O'Brien, Kirsty; Smith, Susan M.; Harrington, Patricia; Ryan, Mairin; O'Neill, Michelle
​Summary: This rapid review aimed to identify measures available to support those in isolation or quarantine during the coronavirus disease 2019 (Covid‐19) pandemic, and determine their effectiveness in improving adherence to these recommendations and or reducing transmission. The rapid review consisted of two elements, the first was a review of guidance published by national and international agencies relating to measures to support those in isolation (due to case status) or quarantine (due to close contact status) during the Covid‐19 pandemic. Five categories of support measures were identified in the international guidance, they were: Psychological, addiction and safety supports, Essential supplies, Financial aid, Information provision and Enforcement. The second element was a rapid literature review of the effectiveness of measures used to support individuals in isolation or quarantine during any pandemic or epidemic setting, due to respiratory pathogens. A systematic search of published peer‐reviewed articles and nonpeer‐reviewed pre‐prints was undertaken from 1 January 2000 to 26 January 2021. Two Australian publications met the inclusion criteria, both based on data from a survey undertaken during the 2009 H1N1 pandemic. The first reported that 55% of households were fully compliant with quarantine recommendations, and that there was increased compliance reported in households that understood what they were meant to do compared with those who reported that they did not (odds ratio [OR]: 2.27, 95% confidence interval [CI]: 1.35–3.80). The second reported that access to paid sick and or carer's leave did not predict compliance with quarantine recommendations (OR: 2.07, 95% CI: 0.82–5.23). Neither reported on reduction in transmission.